PENGARUH GREEN MARKETING TERHADAP MINAT BELI PRODUK FOOD AND BEVERAGE DI STARBUCKS BSD - Pratama, Felix; Sarudin, Rendy (Jurnal Ilmiah Global Education, 2023)
The research conducted to determine the effect of green marketing on buying interest in the food and beverage product at Starbucks BSD. This research was Conducted using quatitive method with questionnaire method distributed via Google Form. One of the analysis technique because in this study only had one X variable and one Y variable. The result pf this study can be seen that (1) green marketing has a significant influence on buying interest at Starbucks BSD. This can be proven from the result of the T test Count > T table of 18.975 > 1.290 (2) From the simple linear regression value the significance value of 0.00 is less than 0.05 (3) from R Square has a value .786 states the effect of the variable 78.6% and 21.4% is influenced by other variables that are not examined.